Konsep Hasrat Perspektif Deleuze dan Al-Ghazali (Analisis Perbandingan Makna Hasrat dalam Psikologi) - Jarman Arroisi; Ahmad Rizqi Fadlilah (Universitas Muhammadiyah Purwokerto (UMP), 2022)
Desire is becoming an increasingly intense discussion in this era. Not only that, desire is even considered to be the main paradigm of social life. Gilles Deleuze is one of those Western thinkers who focused on the problem of desire. In Islam, there is al-Ghazali who is also no less focused on desire. With a descriptive-comparative method and a philosophical approach, this paper intends to examine the conceptual comparison between the two figures.The results of the analysis show that there are similarities in thought between Deleuze and al-Ghazali, those are (i) Both agree that desire is mechanical and moving, (ii) both agree that desire has an important role in human life, (iii) they both share the view that desire is an entity that must exist in humans. The differences are (i) first, in terms of paradigm. Deleuze describes desire in a completely immanent and materialist paradigm. As for al-Ghazali, he explained desire with a divine (revelation) -philosophical paradigm. Second, Deleuze views desire as something completely positive and creative. As for al-Ghazali, although desire has a positive role, it still needs to be controlled. Because in essence, the nature of desire is bad. Third, Therefore, for Deleuze, desire needs to be freed from various constraints such as social norms, customs, or religion. Meanwhile, according to al-Ghazali, desire needs to be controlled through the mujahada. Fourth, for Deleuze, his idea of desire is not in line with moral values, but it is still ethical. Meanwhile, according to al-Ghazali, human desire should be controlled so that he becomes a moral individual.